The reality of antimicrobial resistance and antibiotic usage data in Asia: the CAPTURA experience - Leslie, Toby; Parry, Claudia; Ondoa, Pascale; Walsh, Timothy; Moore, Catrin; Poudyal, Nimesh; Marks, Florian; Gordon, N Claire (Clinical infectious diseases, 2023)
Antimicrobial resistance (AMR), particularly in low- and middle-income countries, is threatening to undermine advances in health and development. Scarce technical and human resources in these countries limit the collection of quality AMR data for evidence-based decision-making. The CAPTURA consortium, funded by the Fleming Fund, was implemented across 7 countries in the South and Southeast Asian region. The program focused on collating historical bacteriological data for qualitative and quantitative analyses. The team gathered standard data on the quality of laboratories and clinics and the quality and quantity of retrospective historical AMR data. In addition, retrospective data on antimicrobial use and consumption were analyzed. While standard protocols guided the project, a tailored approach for stakeholder engagement was implemented to work with countries and secure data-sharing agreements. The program also had to navigate the challenges of the COVID-19 pandemic, making some innovative adaptations to overcome logistical barriers. From 2018 through 2022, a large body of data was collected that was used to base a series of recommended key measures for strengthening the development of standardized national surveillance programs and to support alignment with international efforts.